2014
DOI: 10.17827/aktd.81826
|View full text |Cite
|
Sign up to set email alerts
|

Gilbert\\\\\\\'s Sendromu

Abstract: Gilbert's syndrome is a benign condition that does not progress to chronic liver disease or fibrosis. Gilbert's syndrome diagnosis should be considered in patients with chronic elevation of unconjugated bilirubin. In these patients the presence of hemolysis and other diseases of the liver should be excluded. Gilbert's syndrome is an autosomal recessive disease. The mutation of uridine diphosphate glucuronyl transferase is seen in 10-16% of the population. There is a 70-80% decrease in bilirubin glucuronidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
(103 reference statements)
0
2
0
Order By: Relevance
“… 87 Therefore, sequel to the antioxidant property of bilirubin, 88 90 and its ability to function as a cellular antioxidant, 86 , 91 epidemiological studies have shown that levels of plasma bilirubin are inversely correlated with the risk for the development and progression of both chronic kidney disease and cardiovascular disease. 88 , 89 , 90 , 92 96 Therefore, in the absence of liver disease, high levels of total bilirubin, as observed in this study, may confer some health benefits. 92 , 95 , 97 …”
Section: Discussionmentioning
confidence: 55%
“… 87 Therefore, sequel to the antioxidant property of bilirubin, 88 90 and its ability to function as a cellular antioxidant, 86 , 91 epidemiological studies have shown that levels of plasma bilirubin are inversely correlated with the risk for the development and progression of both chronic kidney disease and cardiovascular disease. 88 , 89 , 90 , 92 96 Therefore, in the absence of liver disease, high levels of total bilirubin, as observed in this study, may confer some health benefits. 92 , 95 , 97 …”
Section: Discussionmentioning
confidence: 55%
“…21 Gilbert syndrome is an autosomal recessive hereditary disease, which is characterized by raised serum indirect bilirubin levels. 22 There is less incidence of atherosclerotic cardiovascular disease in patients with GS, and for these patients, increased bilirubin levels are shown to be negatively correlated with aortic stiffness. 23 In our study, we did not investigate a diagnosis of GS in the patients.…”
Section: Discussionmentioning
confidence: 98%